Leukopenia and Neutropenia at Birth and Sepsis in Preterm Neonates of <32 Weeks' Gestation - Shah, Jyotsna; Balasubramaniam, Tharshini; Yang, Jie; Shah, Prakesh S. (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate associations between leukopenia or neutropenia at birth and risk of sepsis in very preterm neonates.Study Design We conducted a retrospective unmatched cohort study of neonates of <32 weeks' gestation. Those with leukopenia (≤5,000/µL) were compared with a unmatched cohort without leukopenia. Comparisons were also made for patients with neutropenia and without neutropenia. The outcomes were early-onset sepsis, late-onset sepsis, and mortality.Results We identified 271 neonates with leukopenia at birth and 271 without. Multivariable analyses identified higher odds of early-onset sepsis (adjusted odds ratio [AOR] = 4.85, 95% confidence interval [CI]: 1.29–18.20) in leukopenic neonates. Of neonates with leukopenia, 183 had both leukopenia and neutropenia and were associated with the highest odds of early-onset sepsis (AOR = 6.94, 95% CI: 1.77–27.15) compared with those with neither or with either alone.Conclusion Leukopenia, neutropenia, and both leukopenia and neutropenia at birth were associated with early-onset sepsis in very preterm neonates.Key Points
Keywords: infant; premature; early-onset sepsis; late-onset sepsis; mortality